Numerical simulation of the instability line based on laws of physics (2011)
This work presents a numerical study of the instability line that relies on balance laws of physics rather than phenomenology.The instability line defines the onset of static liquefaction for loose sandy materials in the p-q space of effective stresses under undrainedloading conditions. The onset of static liquefaction is predicted by means of a recently developed criterion and specialized to an elastoplastic constitutive model. The performance of this criterion is compared with laboratory tests showing satisfactory results. For a given void ratio and different mean pressures, it is found that the mobilized friction angle at the onset of static liquefaction is not constant. Therefore, the instability line is not an intrinsic property of the sand, but depends on the current state of the material. This work re-interprets the hypothesis given by VaidandChern, which has been amply used to analyze liquefaction phenomena.